Camel Milk: Antimicrobial Agents, Fermented Products, and Shelf Life - Nejat Shifamussa Hamed; Mustapha Mbye; Mutamed Ayyash; Beyza Hatice Ulusoy; Afaf Kamal-Eldin (Foods, 2024)
The camel milk (CM) industry has witnessed a notable expansion in recent years. This expansion is primarily driven by the rising demand for CM and its fermented products. The perceived health and nutritional benefits of these products are mainly responsible for their increasing popularity. The composition of CM can vary significantly due to various factors, including the breed of the camel, its age, the stage of lactation, region, and season. CM contains several beneficial substances, including antimicrobial agents, such as lactoferrin, lysozyme, immunoglobulin G, lactoperoxidase, and N-acetyl-D-glucosaminidase, which protect it from contamination by spoilage and pathogenic bacteria, and contribute to its longer shelf life compared to bovine milk (BM). Nevertheless, certain harmful bacteria, such as Listeria monocytogenes, Yersinia enterocolitica, and Escherichia coli, have been detected in CM, which is a significant public health concern. Therefore, it is crucial to understand and monitor the microbial profile of CM and follow good manufacturing practices to guarantee its safety and quality. This review article explores various aspects of CM, including the types of beneficial and harmful bacteria present in it, the composition of the milk, its antimicrobial properties, its shelf life, and the production of fermented CM products.